Foreign currency borrowing, exports and firm performance: evidence from a currency crisis - Bougheas, Spiros; Lim, Hosung; Mateut, Simona; Mizen, Paul; Yalcin, Cihan (Taylor & Francis, 2018)
This paper develops a simple signaling model of foreign currency borrowing that yields predictions about firm survival and performance during a currency crisis. Using a large panel of firm level data for South Korea we offer empirical support for many of the predictions of our model, while others support predictions that cannot be tested using our data. Our paper demonstrates that although firms that borrow in foreign currency are more likely to exit after the currency collapses, those that continue to produce perform better. Among them, the best performers are exporters whose foreign sales are more competitively priced under a devalued currency.